Prevalence of agr Dysfunction among Colonizing Staphylococcus aureus Strains - Shopsin, Bo; Drlica-Wagner, Alex; Mathema, Barun; Adhikari, Rajan P.; Kreiswirth, Barry N.; Novick, Richard (The Journal of infectious diseases, 2008)
Mutations in the staphylococcal virulence regulator gene agr frequently occur during Staphylococcus aureus infection. Whether agr-defective strains are fit for colonization, an important prerequisite for infection, is unknown. Screening by means of assays to detect δ-hemolysin activity and agr autoinducing peptide production indicated that 15 (~9%) of 160 healthy human subjects were colonized with an agr-defective strain or a mixture of agr-positive and -defective S. aureus strains. The presence of identical agr-defective strains in family members suggests that these strains are transmissible. Additionally, carriage of an agr-defective strain was associated with hospitalization, raising the possibility that such strains may be selected in a nosocomial setting.